Culture of Origin, Parenting, and Household Labor Supply - Ylenia Brilli; Simone Moriconi (CESifo GmbH, 2024)
This paper analyzes how culture affects the engagement of parents in child-rearing activities, and time allocations of parents inside the family. We use data from the World Value Survey to construct a country-specific measure of the value attached to obedience as a child quality, which we associate with the actual parenting behavior and time investments of first-and second-generation migrant parents in Australia. We show that migrant parents from countries in which obedience is more valued as an important child quality, are more likely to be warm and to enact discipline in their parent-child interactions. We also show that a higher value of obedience in the country of origin is associated with a shift of parental time from general care to playing activities, and from the weekdays to the weekends. These results are robust to a large set of sensitivity analyses, which account for omitted variable bias and selection. Finally, we provide evidence that this cultural value may feature a more egalitarian allocation of parenting vs. labor supply tasks at the household level, by increasing fathers' parental time and mothers' labor supply at the intensive margin. We interpret this as indirect evidence that fathers may have a greater marginal utility from parenting time than mothers, on average.
Keywords: D10; J13; J15; J22; Z13; 330; culture; parental investments; parenting; labor supply